Analysis of Reactive Power Compensation Capacity in Urban Mass Transit Power Supply System - ZHOU Weizhi (机车电传动)
According to the reactive power analysis of urban mass transit supply system, it was expounded that for the reactive power compensation calculation, the power quality evaluation point and power factor value should be clear firstly, and the average monthly power factor calculation with initial operation load should be based, also, the low-voltage APF and regenerative energy absorption effected on the reactive power compensation should be considered too, which helped to reduce the installation capacity of concentration reactive compensation and reach reasonable resource configuration.